SISTEM INFORMASI ABSENSI DAN PENGGAJIAN DENGAN MEMANFAATKAN RFID READER (STUDI KASUS : PT. USAHA MANDIRI EKSPORTAMA) - Rusito, Rusito; Rurin Masnunah (MANAJEMEN, 2021)
Information technology is not only expected to be a supporting device and facilitate the company's operational activities, but has become part of the strategy in maintaining employee performance. PT. Usaha Mandiri Exporttama is a company engaged in assembling and manufacturing gas stoves for export destinations with a total of ± 150 employees. Having problems in terms of: (1) Efficiency, (2) Data Accuracy, (3) Timeliness, (4) Data Search, (5) Data Calculation. Seeing the weaknesses in the company, researchers designed a web-based attendance and payroll information system using the PHP programming language and MySQL database. The Rfid Reader and Card/Tag tools were selected to facilitate employee attendance in large numbers. The Information System will immediately record as soon as the card is attached to the Rfid Reader. In this study, researchers used the research method of the Borg and Gall (1987) model from 10 steps to 6 steps. The test results related to the design show the final value of the calculation is 3.0, then the system is declared valid. The validation test by system experts related to usage shows the final value of the calculation is 2.9, concluding that the system is very feasible to use. User Validation at PT. Usaha Mandiri Exporttama Semarang obtained the final value of the calculation is 3.5 stating that the system is feasible to use and very good. The performance test by 4 respondents of the old system and the new system with an average of 43.7% of the old work system, and 87.5% of the new work system showed that the new system was effective and efficient.